The Effect of Perceived Quality in E-commerce to Customer Loyalty (WOM, INTENT, TRUST) Through Customer Satisfaction - Tiurida Lily Anita (Program Studi Hospitality dan Pariwisata, 2019)
ABSTRACTThe objectives of this research was to investigate : (a) the effect of ease of use to customer satisfaction, (b) the effect of web design to customer satisfaction, (c) the effect of responsiveness to customer satisfaction, (d) the effect of personalization to customer satisfaction, (e) the effect of assurance to customer satisfaction, (f) the effect of customer satisfaction to WOM, (g) the effect of customer satisfaction to intent, (h) the effect of customer satisfaction to trust. The design of this research applies a survey toward unit of analysis on website of Hotel Grand Hyatt Jakarta to interview the customers for testing hypothesis. Meanwhile the required data consist of nine variables; ease of use, web-design, responsiveness, personalization, assurance, customer satisfaction, WOM, intent and trust. The aggregate numbers of customer being respondent of the study are 175. Data analysis used in this research was using Structural Equation Modelling (SEM) runs by AMOS 7.0 as software. The result of this research conclude that variable of ease of use, web design, responsiveness, personalization, and assurance attributes had a positive effect to customer satisfaction, and variable customer satisfaction had positive effect to Customer loyalty’s dimensions, which are WOM, intent and trust. Keywords ; Perceived Quality, Customer Satisfaction, Customer Loyalty